The Digital Transformation of Sufi Orders in Indonesia: A Typology of Cyber Sufism - M. Agus Wahyudi; Sehat Ihsan Shadiqin; Eka Srimulyani (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Despite the rapid expansion of digital religious platforms, little is known about how Indonesian Sufi orders have adapted their spiritual practices to cyberspace. This study examines the development of Cyber-Sufism in Indonesia by identifying the typology of digital practices among Sufi orders. Using virtual ethnography and qualitative content analysis, it analyzes the official websites and digital platforms of nine Indonesian Sufi orders selected through purposive sampling. The findings identify two major types of Cyber-Sufism. The informative type, represented by the Qadiriyya wa Naqshbandiyya, Shadhiliyya, Tijaniyya, Syattariyya, Idrisiyya, Sammaniyya, and Rifa'iyya orders, primarily employs digital media for one-way dissemination of Sufi teachings, literature, organizational information, and institutional activities. Meanwhile, the interactive type, represented by the Naqshbandi Haqqani order, enables reciprocal spiritual engagement through online bayʿah, dhikr, ṣuḥbah, spiritual consultation, and virtual religious gatherings. The study concludes that the Naqshbandi Haqqani order exemplifies the most comprehensive model of interactive Cyber-Sufism through its digital zāwiya, which facilitates continuous spiritual learning, guidance, and religious engagement in the digital sphere. Contribution: This study contributes to understanding the transformation of Sufi authority, religious learning, and spiritual interaction in the digital age, while offering a conceptual framework for mapping contemporary digital Sufism in Indonesia.